A novel tubular membrane reactor for pure hydrogen production in the synthesis of formaldehyde by the silver catalyst process. (18th June 2021) - Jokar, S.M.; Keshavarz, M.R.; Zhubin, M.; Parvasi, P.; Basile, A.
Abstract: Formaldehyde-based chemistry plays a significant role in the production of different materials. In this work, attempts have been made to revamp a silver catalyzed formaldehyde plant by applying membrane technology. The conventional silver catalyst packed bed reactor was replaced by a shell and tube membrane reactor. A steady-state one-dimensional model was applied to evaluate the performance of the proposed membrane process. The model was validated with experimental results from the plant. The effects of various parameters including reactor pressure, feed temperature, and membrane thickness on the membrane reactor were investigated. Results showed that the effect of feed temperature on production rates was negligible. The increase in pressure and decrease in membrane thickness, however, leads to increase products. The simultaneous production of 100 tonnes/day of formalin 37% (37 wt% formaldehyde in water) and 500 kg/day pure hydrogen achieved by the proposed process. Furthermore, the exiting reactor temperature can be reduced to 420 °C which is significantly lower than the conventional method (650 °C). Highlights: The silver process for formaldehyde production in a formaldehyde plant was modeled. A novel tubular membrane reactor was modeled for formaldehyde synthesis. The simultaneous production of pure H2 (500 kg/d) and formalin (1000 t/d) was achieved. The process temperature decreased by 650 °C to 420 °C by membrane reactor.